A compreensão da consciência moral segundo Marciano Vidal Garcia - Almeida, Frank Antonio de (2013)
The present thesis aims to reveal some conceptual aspects in the formation of conscience mortal seen through the eyes of the moral theologian Marciano Vidal Garcia. Undoubtedly these aspects are rooted in the itinerary of his personal and academic life, as well we understand that the formation of conscience happens in life-history and process of the individual academic. Therefore, this work speaks at beginning chapter on the path of theological reflection and experiential conducted by the author. Surely his university studies are relevant and his constant concern in dialogue with issues related to moral theology, process in search of a better understanding of the moral conscience. His ongoing theological dialogue with the authors Bernahrd Haring and Alphonsus Liguori was decisive in the formation of their paradigm about moral conscience. The academic experience of Marciano Vidal at various universities and their life experience showed in his writing new paradigms to better understand the issue we reviewed. In this path toward the understanding of moral conscience, we meet the elements: Conscientiousness. Moral. Ethics. Moral crisis. Moral education. Christian Ethics